Medio-lateral inclination of proximal and distal articular surface of the radius - Al-Imam, Ahmed (Asian Journal of Medical Sciences, 2016)
Background: The radius, also known as the radial bone, is the shorter of the two bones of the forearm. It has proximal and distal articulations with the humerus, ulna, and carpal bones. It is almost universally present,as a skeletal blueprint, in eachtetrapod’s forelimb. The detailed morphometry of radius, has not been fully explored. Specifically, the inclination of its proximal and distal articular surfaces, which can be affected in many pathologies including: fractures-dislocations, joint’s degenerations, tumors, dystrophic calcifications, and pathologic deposits. Aims and Objectives: To derive a statistical inference concerning the inclination of the proximal and distal articular surface of radius. Materials and Methods: In a sample of 30 dry specimens of human radial bone (radius), measurements were done to derive statistical inference concerning: the inclination of proximal and distal articular surfaces (P and D), length of radius (L), mid-point thickness (T), length of head of radius (HL). Materials used for measurements included: electronic Vernier, digital inclinometer, and a tape measure. The most challenging parameter to be measured, was the inclination of articular surfaces, which required multiple reference points: at the interosseous border of radius, proximal and distal ends of radius. Results: The mean values (+/- standard deviation) were: 22.23 +/- 1.89 cm (L), 1.43 +/- 0.2 cm (T), 0.95 +/- 0.135 cm (HL), 6.283 +/- 3.253 (P), and 23.77 +/- 1.874 (D). The 95% Confidence Interval was: 0.90 to 1 (HL), 5.07 to 7.50 (P), and 23.07 to 24.47 (D). Linear regression was absent between most of the studied parameters, with exception for the correlation between the inclination of the proximal articular surface and the value of (P/HL), which revealed a Correlation coefficient (r): 0.958, and the relevant p-value is < 0.00001 (significant at p< 0.01). Conclusion: This study is in line with prior studies concerning the morphometry and inclination of radial articular surfaces. It has a tremendous value in biomedical science, biomechanical applications and prosthesis synthesis, corrective surgical and orthopedic procedures, anthropology, and forensic sciences. Asian Journal of Medical Sciences Vol.7(5) 2016 117-123